House made of dawn - Momaday, N. Scott (Harper & Row, 1968)
A young Native American, Abel has come home from war to find himself caught between two worlds. The first is the world of his father$1 (Bs, wedding him to the rhythm of the seasons, the harsh beauty of the land, and the ancient rites and traditions of his people. But the other world$1 (Bmodern, industrial America$1 (Bpulls at Abel, demanding his loyalty, trying to claim his soul, and goading him into a destructive, compulsive cycle of depravity and disgust.s
Keywords: Historical Fiction; Native American Literature